Genetic Evidence Supporting the Causal Role of Homocysteine in Chronic Kidney Disease: A Mendelian Randomization Study - Xiong, Yang; Zhang, Yangchang; Zhang, Fuxun; Wu, Changjing; Luo, Peiyi; Qin, Feng; Yuan, Jiuhong (Frontiers in Nutrition, 2022)
Background: The causal relationship between homocysteine (Hcy) levels and chronic kidney disease (CKD) remains unclear. This study was performed to estimate the potential causal effects of Hcy on the estimated glomerular filtration rate (eGFR) and CKD. Materials and Methods: The single nucleotide polymorphisms (SNPs) associated with one standard deviation (SD) Hcy increase were identified using the genome-wide association study (GWAS). The summary statistics of the eGFR and CKD were from the CKDGen project in the European ancestry and the Population Architecture using Genomics and Epidemiology (PAGE) project in the non-European ancestry. Two-sample Mendelian randomization analyses were used in this study to verify the causal effects between Hcy, eGFR, and CKD. Results: Genetically predicted 1-SD Hcy increase was causally associated with eGFR decline in the CKDGen project (β = -0.027 log mL.min-1/1.73 m2, P < 0.01 for the overall cohort; β = -0.028 log mL.min-1/1.73 m2, P < 0.01 after excluding the diabetic patients). 1-SD Hcy increase was also associated with a 1.32-fold risk of CKD in the PAGE project (95% CI = 1.06-1.64, P < 0.05). The association was directionally similar in the CKDGen project (OR = 1.08, 95% CI = 0.97-1.44, P = 0.098). The pooled odds ratio of CKD was 1.24 (95% CI = 1.07-1.44, P < 0.05) per 1-SD Hcy increase. Conclusion: Using genetic data, Hcy increase is causally associated with renal function injury and further CKD.